IMPLEMENTASI IZIN MENDIRIKAN BANGUNAN DI KABUPATEN KAMPAR BERDASARKAN PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 4 TAHUN 2014 TENTANG BANGUNAN GEDUNG - Riyad Fauzura; Mexsasai Indra; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Kampar Regency Government issued Kampar Regency RegionalRegulation Number 4 of 2014 concerning Buildings to regulate building permits,precisely in Article 16 paragraph 1 letter (a) which states that every person orlegal entity including government agencies must submit an IMB application to theRegent to carry out building construction activities and/or building infrastructure.However, after the enactment of the regional regulation, there are still manyviolations that occur in the implementation of buildings in Kampar Regency, atotal of 156 buildings that were put in order by Satpol PP as of 2019-2021. Thepurpose of this thesis research is first, to determine the implementation of buildingpermits in Kampar Regency based on Kampar Regency Regional RegulationNumber 4 of 2014 concerning Building Buildings. Second, to find out theinhibiting factors in the implementation of the Building Permit rules in KamparRegency. Third, to find out the efforts in overcoming obstacles in theimplementation of building permit rules in Kampar Regency.From the results of the study, it was concluded that, first, theimplementation of building permits in Kampar Regency based on KamparRegency Regional Regulation Number 4 of 2014 concerning Buildings has notgone well. Second, the inhibiting factors in the implementation of the BuildingPermit rules in Kampar Regency are the area, budget and socialization,coordination between Satpol PP and related agencies, the role of the community,and community legal awareness. Third, efforts to overcome obstacles in theimplementation of the Building Permit rules in Kampar Regency, namely satpolPP providing education to the community and inviting the community to play anactive role in reporting on buildings that do not have a permit, the need to reportwith the Kampar Regency DPRD regarding budget problems, forming a judicialteam which is a combination of all related agencies led by Kasat Satpol PP.DPMPTSP in the future will educate the public so that the community can betterparticipate in supervising the implementation of buildings. Then the DPRD willapproach and socialize the Regional Regulation to the community from theDistrict level to the Village level and call relevant parties to record how theimplementation of the Regional Regulation and tighten up how to follow up on theproblem.Keywords: Implementation, Regional Regulation, Building Permit.